How bacteria actively use passive physics to make biofilms - Chai, Liraz; Zaburdaev, Vasily; Kolter, Roberto (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Modern molecular microbiology elucidates the organizational principles of bacterial biofilms via detailed examination of the interplay between signaling and gene regulation. A complementary biophysical approach studies the mesoscopic dependencies at the cellular and multicellular levels with a distinct focus on intercellular forces and mechanical properties of whole biofilms. Here, motivated by recent advances in biofilm research and in other, seemingly unrelated fields of biology and physics, we propose a perspective that links the biofilm, a dynamic multicellular organism, with the physical processes occurring in the extracellular milieu. Using Bacillus subtilis as an illustrative model organism, we specifically demonstrate how such a rationale explains biofilm architecture, differentiation, communication, and stress responses such as desiccation tolerance, metabolism, and physiology across multiple scales—from matrix proteins and polysaccharides to macroscopic wrinkles and water-filled channels.
CRIS-Team Scopus Importer:2024-10-11
Keywords: biofilms; ECM; liquid–liquid phase separation; metal ions; water transport